Colonization of carbapenem-resistant Enterobacteriaceae (CRE) among the patients admitted in the intensive care unit: an observational study - M. Prabhu; L. Ranganathan; V. Tiru; S. Shyamsundar (Вестник интенсивной терапии)
INTRODUCTION: Carbapenem-Resistant Enterobacteriaceae (CRE) are a family of bacteria that has the propensity to cause community-acquired and healthcare-associated infections. Patients colonized with CRE are shown to have higher mortality rates, increased length of hospital stay, and increased risk of infection transmission to other patients and healthcare workers. OBJECTIVE: Hence, this study was conducted to identify CRE colonization among patients admitted in the intensive care unit (ICU) and to evaluate the factors associated with CRE colonization. METHODS: This was an observational, cross-sectional study, conducted in the ICU of a secondary care hospital in Chennai, from September 2020 to August 2021. Patients > 18 years of age and ICU stay > 24 hours were included. Generic details like patients’ age, gender, diagnosis, comorbid conditions and specific details like previous hospitalization and antibiotic usage were collected. CRE colonization was assessed by rectal swabs. Results of the swab tests, organism detected and carbapenem sensitivity were noted down. RESULTS: Out of 874 admitted to the ICU, 188 patients met the inclusion criteria and were included in the study (108 males (57.4 %); 80 females (42.6 %), mean age 63.6 years). 197 culture isolates were obtained, of which 135 were E coli, 55 were Klebsiella pneumoniae and 4 were Enterococcus spp. Enterobacter spp., Proteus mirabilis and Klebsiella oxytoca were found in 1 patient each. Out of the 193 Enterobacteriaceae culture isolates, 31 were resistant to carbapenems, a proportion of 16.1 %. There were no significant associations between age, gender, presence of comorbidities and history of major surgery and CRE colonization. History of previous hospitalization (p < 0.01), previous use of antibiotics (p < 0.01) and the use of indwelling catheters (p < 0.01) showed statistically significant association with CRE colonization. CONCLUSIONS: Usage of appropriate antibiotics, prompt de-escalation and avoidance of excessive broad-spectrum antibiotics are important in averting the development of carbapenem-resistant organisms. The identification of CRE colonization in ICU patients is important, as implementation of appropriate measures can prevent spread of infection.